Flower production of apple varieties grown by different environmental technologies - Dremák, P. (International Journal of Horticultural Science, 2010)
The flower production of four apple varieties have been observed grown in integrated and in ecological growing technologies during the spring of 2010. The trees produced in the last year (2009) nearly similar yields, so the effect of the technologies may causen differences in the production of flowers. According to our results, the ecological technology produced higher flower densities in the majority of variables, which was in relation with the vigor, branching and thickening of the trunks. The varieties observed displayed substantial differences in the appearance of fruiting structures of different age on the branches. This information may prove to be essential for the decisions to be made in timing and severity at the pruning operations.